PENERAPAN PEMBERIAN LATIHAN SOAL-SOAL KONTEKSTUAL DALAM MENINGKATKAN HASIL BELAJAR MATEMATIKA - Agus Purwantoro; B Saryantono (Universitas Muhammadiyah Lampung, 2020)
The learning process involves three important components, namely subject matter, learning activities and assessment (evaluation). Planning each learning scenario needs to always keep in mind the nature of the material to be studied by students, student readiness factors, and student motivation to learn, because what students will learn must be aware of the meaning and benefits for students and for their future lives. Efforts to raise the motivation of class XI students of SMA Negeri 1 Natar South Lampung in learning mathematics have been carried out by teachers in their field of study in various ways, such as providing opportunities for students to ask questions, and designing learning in the form of group discussions. Based on the fact that t arithmetic is between t < t with a significant level of 5%, the value of t = 0.98 < t = 1.76 so that Ho is accepted, the study shows that the average ability of students in the initial test of ability to learn mathematics has increased.